A Compact Flexible Frequency Reconfigurable Antenna for Heterogeneous Applications - Hussain, N; Awan, WA; Naqvi, SA; Ghaffar, A; Zaidi, A; Naqvi, SA; Iktikhar, A; Li, XJ (IEEE, 2020)
This paper presents a compact frequency reconfigurable antenna for flexible devices and conformal surfaces. The antenna consists of a simple easy to fabricate structure consisting of a stub loaded circular radiator, designed on commercially available RT5880 flexible substrate (εr = 2.2) with a thickness of 0.254 mm. The combination of stub loading and slot etching techniques are utilized to achieve the advantages of compactness, frequency reconfigurability, wide impedance bandwidth, and stable radiation pattern with structural conformability. The frequency reconfigurability is achieved by employing two p-i-n diodes. Simulated and experimental results showed that the antenna operates in various important commercial bands, such as S-band (2 GHz– 4 GHz), Wi-Max (3.5 GHz and 5.8 GHz), Wi-Fi (3.6 GHz, 5 GHz, and 5.9 GHz), 5G sub-6-GHz (3.5 GHz and 4.4 GHz – 5 GHz), and ITU-band (7.725 GHz – 8.5 GHz) with the additional advantages of structural conformability. Furthermore, the performance comparison of the proposed flexible antenna with the state-of-the-art flexible antennas in terms of compactness, frequency reconfigurability, and number of operating bands demonstrates the novelty of the proposed antenna and its potential application in heterogeneous applications.
Keywords: CPW-fed; Conformability; Frequency reconfigurable; Heterogeneous applications; Miniaturized; Multiband; Portable; Wideband